Vectorized Delivery of Alpha-GalactosylCeramide and Tumor Antigen on Filamentous Bacteriophage fd Induces Protective Immunity by Enhancing Tumor-Specific T Cell Response - Sartorius, Rossella; D’Apice, Luciana; Barba, Pasquale; Cipria, Deborah; Grauso, Laura; Cutignano, Adele; De Berardinis, Piergiuseppe (Frontiers in Immunology, 2018)
We have exploited the properties of filamentous bacteriophage fd to deliver immunologically active lipids together with antigenic peptides. Filamentous bacteriophages resemble for size, capability to be permeable to blood vessels and high density antigen expression, a nature-made nanoparticle. In addition, their major coat protein pVIII, which is arranged to form a tubular shield surrounding the phage genome, has a high content of hydrophobic residues promoting lipid association. We conjugated bacteriophages to alpha-GalactosylCeramide (-GalCer), a lipid antigen stimulating invariant Natural Killer T (iNKT) cells and capable of inducing their anti-tumoral activities. We found that bacteriophage fd/-GalCer conjugates could repeatedly stimulate iNKT cells in vitro and in vivo, without inducing iNKT anergy. Moreover, co-delivery of alpha-GalactosylCeramide and a MHC class I restricted tumor associated antigenic determinant to APCs via bacteriophages strongly boosted adaptive CD8+ T cell response and efficiently delayed tumor progression. Co-delivery of a tumor antigen and iNKT-stimulatory lipid on the surface of filamentous bacteriophages is a novel approach to potentiate adaptive anti-cancer immune responses, overcoming the current limitations in the use of free alpha-GalactosylCeramide and may represent an attractive alternative to existing delivery methods, opening the path to a potential translational usage of this safe inexpensive and versatile tool.